TikTok dan Konstruksi Branding Tempat : Studi Kualitatif Blok M sebagai Ruang Gaya Hidup Anak Muda - Salman Salman; Hanum Salsabila; Zhafirah Muthmainnah Giani (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study aims to analyze the role of TikTok in shaping young people's perceptions of the Blok M area's branding as a contemporary lifestyle destination. The study employed a qualitative approach with a constructivist paradigm through in-depth interviews with five informants, supported by non-participatory observation and documentation. The results indicate that TikTok serves as both an initial trigger and a reinforcement in the perception-forming process. Visual and narrative representations circulating on TikTok construct the image of Blok M as a dynamic, creative urban space, closely aligned with the values ​​of self-expression, freedom, and youth community. This study also found a cyclical relationship between digital and in-person experiences, where exposure to TikTok content influences visitation intentions, while on-site experiences reinforce or adjust initial perceptions. While most informants perceived a match between expectations and reality, there were also discrepancies, such as more crowded conditions and exaggerated expectations. These findings confirm that place branding is increasingly influenced by user-generated content and the dynamics of participatory media. Thus, TikTok plays a cultural mediator in shaping regional identity in the digital age.